Boron and tin doping of Ni-MCM-41 catalysts for dry reforming - Tan, Humphrey Wei Ming. (2010)
This project investigates the promotion of Ni-MCM-41 using boron or tin as promoters. MCM-41 mesoporous molecular sieves were synthesized by conventional hydrothermal synthesis. Nickel nitrate, boric acid and tin(II) chloride were used as Ni, B and Sn precursor respectively. Nickel catalysts and the promoters were incorporated into the support by wet co-impregnation method. The catalytic properties of B-Ni-MCM-41 and Sn-Ni-MCM-41 were studied for reforming of methane with carbon dioxide. The catalysts were characterized by X-ray diffraction (XRD) and thermogravimetry (TGA) analysis. The results revealed that using 0.5% wt of boron as promoter in B-Ni-MCM-41 benefited the catalysts in term of the catalytic activity and long-term stability. The improved catalytic performance was suggested to be the resultant of lower carbon deposition on the catalysts during the reaction. The boron particles have the ability to anchor themselves on the step sites and subsurface sites during wet impregnation and these sites are also the preferential sites of carbon deposition. On the other hand, results from tin promotion had a detrimental effect on the catalytic performance. The formation of Sn-Ni alloy did not successfully suppress carbon formation. According to density functional theory, the alloy is suggested to increase the diffusion activation energy of carbon atom across the surface. However, alloying also contributes to the lost of active sites. Another source of deposition of carbon through the CH2 chain mechanism might also contribute to the poor performance of tin promoters. Ni-MCM-41 catalysts with boron promotion improved the catalytic activity and provided increased long term stability. Thus, boron served as a promising candidate for promotion of Ni-MCM-41 for methane reforming using carbon dioxide.